Plague ship : a novel of the Oregon files - Cussler, Clive; Du Brul, Jack B. (New York : G.P. Putnam's Sons, 2008)
The crew of the Oregon has just completed a top secret mission against Iran in the Persian Gulf, when they come across a cruise ship adrift in the sea. Hundreds of bodies litter its deck, and as ship captain Cabrillo tries to determine what happened, explosions rack the length of the ship. Barely able to escape with his own life and that of the liner's sole survivor, Cabrillo finds himself plunged into a mystery as intricate--and as perilous--as any he has ever known, and pitted against a cult with monstrously lethal plans for the human race . . . plans he may already be too late to stop.--From publisher description.
Keywords: Cabrillo, Juan -- (Fictitious character) -- Fiction; Mercenary troops -- Fiction; Suspense fiction; Sea stories